KESEJAHTERAAN PSIKOLOGIS GURU YANG MENDAPATKAN SERTIFIKASI - Rini Indryawati (Universitas Gunadarma, 2014)
The aim of this research is to describe why does someone interested in to be a teacher, to describe the teacher’s psychological well-being before and after gain the certification, and also the factors influencing it. The teacher’s psychological well-being related to stress, fatigue, and how the teacher copes of those problems. Participant involved in this research are two teachers who already certificated and three significant others. The data gained using interview and non participant observation. Based on the whole findings, this research shows that the teachers have good psychological well-being, both in before and after being certificated. It is showed from the dimensions influencing the psychological well-being such as autonomy, self-acceptance, environmental mastery, positive relation, life focus, and personal growth. Keywords: Psychological well-being, Teacher, Certification